Numerical and experimental study on active aerodynamic deflectors for vortex-induced vibration suppression of a narrow Π-shaped girder section - Han Xiao; Zhiwen Liu; Zhengqing Chen; Fan Li; Julian Unglaub; Klaus Thiele; Fawei He; Yabin Xin (Engineering Structures, 2025)

Multiple defects construction of Co loading on Ni foam to activate water for promoting catalytic ozonation of dichloromethane - Yongtao Li; Chujun Luan; Fawei Lin; Xueyan Zhu; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Chi He (Journal of Hazardous Materials, 2025)

Context dependencies in the responses of plant biomass and surface soil organic carbon content to nitrogen addition and precipitation change within alpine grasslands - Fawei Zhang; Hongqin Li; Jingbin Zhu; Chunyu Wang; Yunlong He; Juntao Zhu; Qiang Yu; Huakun Zhou; Yingnian Li; Naishen Liang (Agriculture, Ecosystems & Environment, 2025)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions - Fawei Lin; Li Xiang; Zhiman Zhang; Na Li; BeiBei Yan; Chi He; Zhengping Hao; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2022)

Alpine grassland plants grow earlier and faster but biomass remains unchanged over 35 years of climate change - Hao Wang; Huiying Liu; Guangmin Cao; Zhiyuan Ma; Yikang Li; Fawei Zhang; Xia Zhao; Xinquan Zhao; Lin Jiang; Nathan J. Sanders; Aimée T. Classen; Jin‐Sheng He (Ecology Letters, 2020)
Satellite data indicate significant advancement in alpine spring phenology over decades of climate warming, but corresponding field evidence is scarce. It is also unknown whether this advancement results from an earlier shift of phenological events, or enhancement of plant growth under unchanged phenological pattern. By analyzing a 35‐year dataset of seasonal biomass dynamics of a Tibetan alpine grassland, we show that climate change promoted both earlier phenology and faster growth, without changing annual biomass production. Biomass production increased in spring due to a warming‐induced earlier onset of plant growth, but decreased in autumn due mainly to increased water stress. Plants grew faster but the fast‐growing period shortened during the mid‐growing season. These findings provide the first in situ evidence of long‐term changes in growth patterns in alpine grassland plant communities, and suggest that earlier phenology and faster growth will jointly contribute to plant growth in a warming climate.

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)